Phytosociological Studies of Woody Vegetation along the Disturbance Gradient in Tropical Dry Deciduous Forest of Hastinapur - Khurana, Poonam (Indian Forester, 2009)
In the present study, various phytosociological attributes of woody vegetation were analyzed along the disturbance gradient in tropical dry deciduous forest of Hastinapur. The sites were surveyed for floristic composition, distribution pattern, species diversity and dominance. Maximum number of trees, seedlings and saplings were recorded for Block-2 and minimum for Hillock. Number of shrub species was maximum on Hillock because of open forest canopy due to disturbances, which provide favorable conditions of growth for shrubs and other weeds. Most of species except shrubs were regular followed by random in distribution pattern. Diversity index and concentration dominance confirmed the disturbances in the studied forest. Beta diversity values were maximum for the Hillock forest.